2012
DOI: 10.26719/2012.18.6.663
|View full text |Cite
|
Sign up to set email alerts
|

Health needs and eHealth readiness assessment of health care organizations in Kabul and Bamyan, Afghanistan

Abstract: This study assessed the need and readiness of health care institutions in Kabul and Bamyan, Afghanistan for successful implementation of information and communication technology in health care (eHealth). A mixed methods design was adopted at 2 institutions in the Aga Khan Development Network in Afghanistan: the French Medical Institute for Children in Kabul and Bamyan Provincial Hospital, Bamyan. Information for the needs assessment was obtained from interviews and focus groups and eHealth readiness was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 9 publications
2
29
0
Order By: Relevance
“…Much as this is so, many studies had failed to observe that health behaviours in developing countries deviate from those of developed nations and as a result, the developed frameworks fell short of following the neoclassical model. Developing countries have high numbers of illiteracy rates, with people that lack basic information and are incapable of processing even the little available information (Durrani et al, 2012;Anwar et al, 2012). The World Trade Organization report (WTO, 2013) also confirmed that, much as there is an increase of the use of IT in a form of mobile phones and internet in many developing countries, this usage is still limited to social communication.…”
Section: 1mentioning
confidence: 90%
See 3 more Smart Citations
“…Much as this is so, many studies had failed to observe that health behaviours in developing countries deviate from those of developed nations and as a result, the developed frameworks fell short of following the neoclassical model. Developing countries have high numbers of illiteracy rates, with people that lack basic information and are incapable of processing even the little available information (Durrani et al, 2012;Anwar et al, 2012). The World Trade Organization report (WTO, 2013) also confirmed that, much as there is an increase of the use of IT in a form of mobile phones and internet in many developing countries, this usage is still limited to social communication.…”
Section: 1mentioning
confidence: 90%
“…www.ejisdc.org As Durrani et al (2012) observed, the success of E-health implementation in developing countries could only be achieved if its cost effectiveness is predetermined before its implementation. However, this necessitates the assessment of its readiness before its implementation could be done (Ojo et al, 2008).…”
Section: The Electronic Journal Of Information Systems In Developing mentioning
confidence: 99%
See 2 more Smart Citations
“…Three key determinants of change implementation were identified: task demands, resource availability, and the situational factors. 4 Durrani, Khoja, Naseem, Scott, Gul, and Jan (2012) [16] To assess the need and readiness for e-health at healthcare facilities in Pakistan 10…”
Section: Not Applicable Qualitativementioning
confidence: 99%